Meningkatkan Hasil Belajar Materi Organ Gerak Manusia dan Hewan Tema 1 Subtema 3 dengan Metode Pembelajaran Problem Based Learning Pada Siswa Kelas 5 SD 2 Burikan Tahun Pelajaran 2022/2023 - Huda, Choirul; Ulfa, Mutiara; Sudadi, Sudadi (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
This Study aims to increase learning outcomes of animal and human movement organs things through a problem based learning model for the sixth grade students of SD 2 Burikan in the first semester of the 2022/2023. The procedure for conducting and implementing the research is divided into three cycles. The results of this study indicate that student learning activities in the frirst cycles average value was 70. 18 or 55,56 %. The average value of the second cycles was 77,03 or 85,18% learning completeness so that it increased by 29,62% from the first cycles. It was concluded that the application of the problem based learning model could increase learning outcomes of animal and human movement organs In grade V SD 2 Burikan Kota Kudus.